O8.5. CORTICAL LOCALIZATION OF SELECTIVE ATTENTION DEFICITS FOLLOWING FIRST PSYCHOTIC EPISODE. (9th April 2019) - Sklar, Alfredo; Coffman, Brian; Olson, Carl; Cho, Raymond; Ghuman, Avniel; Haas, Gretchen; Salisbury, Dean
Abstract: Background: Impairments in selective attention and their neurophysiologic concomitants early in the course of psychotic illness remain relatively understudied. Our recent data provided evidence for disruptions in the attention-related electrophysiological responses among individuals following their first psychotic break (FESz). Specifically, FESz exhibited reduced amplitudes of the N2pc component compared to healthy controls (HC) during a target detection task. The present investigation additionally used the magnetoencephalography (MEG) data that had been simultaneously recorded during selective attention task performance to identify disruptions in source-resolved cortical regions underlying the N2pc impairment. Methods: MEG and EEG were simultaneously recorded from 22 first-episode schizophrenia spectrum (FESz) and 22 healthy control (HC) individuals during two target detection tasks that required different degrees of top-down attentional control; pop-out and visual search. MEG and EEG sensor locations were coregistered with structural MRI scans for each participant and the boundary element method was used to model the forward solution. The inverse solution for cortical activity contributing to the N2pc signal (275 – 325ms post stimulus) was then derived using the noise covariance matrix calculated from the baseline period of each trial. BA7, BA39, and BA37 were selected a priori as regions of interests (ROIs) based on previous investigations of N2pc sources. Average activity during the N2pc time window was compared between groups using a 2 (task condition) x 2 (group) x 3 (ROI) ANOVA. Results: A significant interaction between group and task condition was observed (F1, 42=5.3, p=.03). HC exhibited marginally increased activity during pop-out compared to FESz (t42=1.86, p=.07) despite a statistically equivalent level of activity during visual search (t42=-0.86, p=.39). There were no main effects of group (p=.54), task condition (p=.90), or ROI (p=.94). Nor were there interactions between ROI and group (p=.81) or ROI and task (p=.16). Whereas no correlations between ROI activity and N2pc were observed among FESz (p's>.05), larger BA37 during visual search activity was associated with larger N2pc scalp amplitudes in HC (r=-.65, p=.001). Discussion: In contrast to the simple group difference in N2pc amplitude recorded from the scalp, examination of the cortical dynamics contributing to this response revealed a differential effect of task condition between groups. FESz exhibited reduced activity relative to HC on target pop-out trials compared to those requiring a top-down, serial search of potential target stimuli. While this finding appears counterintuitive, it may reflect a hyperfocusing of attention on distractor stimuli in our FESz group recently described in a study of individuals with schizophrenia. This mechanism would explain the relative preservation of attention-related cortical activity in FESz during a task with increased distractor interference. The difference between our sensor-level N2pc results based on EEG recordings and our source-level cortical activity derived from simultaneously recorded EEG and MEG speaks to the importance of utilizing complementary imaging modalities to enrich our understanding of processes involved in complex cognitive functions.